Design, Synthesis, and Insecticidal Evaluation of New Benzoylureas Containing Isoxazoline and Isoxazole Group - Sun, Ranfeng; Li, Yongqiang; Xiong, Lixia; Liu, Yuxiu; Wang, Qingmin (Journal of agricultural and food chemistry, 2011)
Twenty-two new benzoylphenylureas containing isoxazoline and the isoxazole group were designed and synthesized, and their structures were characterized by 1H NMR and elemental analysis (or HRMS). The larvicidal activities against Oriental armyworm, mosquito, and diamondback moth of the new compounds were evaluated. Compounds I-1 and III-1 showed nearly the same level of insecticidal activity against Oriental armyworm as commercial insecticide Flucycloxuron and surprisingly exhibited much higher larvicidal activities against diamondback moth than Flucycloxuron.